Patient reported experience of blood glucose management when undergoing hyperbaric oxygen treatment. Issue 4 (August 2019) - Baines, Carol; O'Rourke, Geraldine; Miller, Charne; Ford, Karen; McGuiness, William
Abstract: Background: Patients who have diabetes and require hyperbaric treatment for wound healing are an increasing population. Hyperbaric oxygen treatment (HBOT) has been shown to reduce a patient's blood glucose level during an individual treatment. Anecdotal evidence suggests patients with diabetes are concerned about suffering a hypoglycaemic episode during HBOT. It is suspected that patients who have diabetes undertake protective health behaviours by intentionally increasing their blood glucose levels prior to HBOT. Aim: To explore the emotional and physical experiences of patient self-management behaviours of their blood glucose levels during a course of hyperbaric oxygen treatment. Method: The use of semi-structured in-depth interviews, each interview was audio recorded and transcribed verbatim. Participants (n = 15), were prior patients living with diabetes who had undergone HBOT at a tertiary hospital in an Australian state during 2014–2017. Interpretive description along with thematic analysis of all interviews was undertaken. Findings: Four themes emerged from the interviews, each deriving from the participants' experiences 1. Varying recognition of self-management requirement of diabetes; 2. Hypoglycaemia fear; 3 . Treatment-based adaptation; and 4. Ownership / monitoring. Participants reported that they altered their diabetic regime/blood glucose management to undertake a course of HBOT. Discussion: Patient engagement throughout HBOT, leads them to elevate their blood glucose, although not advocated, to above normal levels, adopting these behavioural changes as a self-protective mechanism. Conclusion: Improving the patient experience of hyperbaric oxygen treatment is multifactorial and often dependant on the relationship between the clinician and the patient. Consistent monitoring of blood glucose during HBOT, may ameliorate negative feelings that are often associated with this treatment option.